Future of virtual autopsy in India - Rastogi, AK; Kumar , S (Journal of Indian Academy of Forensic Medicine, 2024)
Presently in India virtual autopsy service is not provided by any center. All India institute io Medical Science, New Delhi is trying to establish virtual autopsy center, they have got the infrastructure established for research purposes. In India many autopsy centres are trying to learn and explore the training related to virtual autopsy, first basic training done national forensic science university at Gandhinagar, Gujarat. Large money, training, and legal hurdles are the main barriers. Initial stage institute of national importance has funding ability to start, then slowly it will on the public demand, it would be started most of the center. As per legalities, the legal system easily adapts the scientific use of technology in the court of justice. X ray examination report taking consideration in various court judgement, indication of the virtual autopsy report is considerable in the court. India has presently two autopsy centers have their own CT scan machine they are utilizing learn for the virtopsy, 1st in AIIMS Delhi and second in St John’s hospital Bengaluru, in future it’s going to established in many autopsies center of India. The possibility of First will be central institute then peripheral institute. In 4 to 5 years, virtual autopsies will be implemented in numerous autopsy centers.